Complications due to Stress Echocardiography - N. N. Mikheyev (Общая реаниматология)
Objective: to assess the prevalence of minor and major complications and side effects during stress echocardiography (stress-EchoCG) in a group of patients with suspected coronary heart disease (CHD).Subjects and methods: The study included 1359 patients with suspected CHD, who had undergone stress EchoCG; the latter using the following standard study protocols (dipyridamole/atropine (n=184), dobutamine/atropine (n=231); transesophageal atrial pacing (TEAP) (n=154), semirecumbent bicycle ergometry (BEM) (n=122)) was performed in 691 patients. Six hundred and sixty-eight patients underwent combined stress-EchoCG using the following study protocols: dipyridamole/TEAP (n=151), dobuta-mine/TEAP (n=243); dipyridamole/dobutamine (n=162), dipyridamole/pair BEM (n=112). The adverse reactions included ventricular and supraventricular premature beats, headache, nausea, and muscle shivering. The minor complications were short (less than 2 minutes) paroxysms of hemodynamically insignificant supraventricular and ventricular tachycardia. The major complications were the development of acute coronary syndrome and ventricular fibrillations.Results: The most common complications during stress EchoCG were rare ventricular premature beats (26.0 and 18.9% in the dobuta-mine and BEM protocols, respectively) headache (16.7% in the dipyridamole protocol). Major complications were noted in two (0.147%) cases. With the use of the standard dipyridamole protocol, one patient developed acute coronary syndrome with ST-segment elevation, which required emergency coronarography and angioplasty of the right coronary artery. When the standard dobutamine/atropine protocol, with 0.25 ml of 0.1% atropine solution being given during the administration of dobutamine at a rate of 40 ^g/kg/min, was used, another patient developed ventricular fibrillation requiring resuscitative measures.Conclusion: Stress EchoCG is generally a safe highly informative noninvasive technique for diagnosing CHD, but it may be attended by adverse reactions caused by stress agents, minor and major complications during testing, which require that patients compulsorily give their informed consent.